2010
DOI: 10.1103/physreva.81.063607
|View full text |Cite
|
Sign up to set email alerts
|

Universality of Brunnian (N-body Borromean) four- and five-body systems

Abstract: We compute binding energies and root-mean-square radii for weakly bound systems of N = 4 and 5 identical bosons. Ground and first excited states of an N -body system appear below the threshold for binding the system with N − 1 particles. Their root-mean-square radii approach constants in the limit of weak binding. Their probability distributions are on average located in nonclassical regions of space which result in universal structures. Radii decrease with increasing particle number. The ground states for mor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 34 publications
5
34
0
Order By: Relevance
“…ER was soon generalized to four-body systems [19,20]. For four identical bosons [21][22][23], it was found that the Efimov trimer and tetramer states always appear as sets of states with two tetramers associated with each of the trimer levels. Experimentally, tetramer states were recently realized in an ultracold gas of cesium atoms [24].…”
Section: Introductionmentioning
confidence: 99%
“…ER was soon generalized to four-body systems [19,20]. For four identical bosons [21][22][23], it was found that the Efimov trimer and tetramer states always appear as sets of states with two tetramers associated with each of the trimer levels. Experimentally, tetramer states were recently realized in an ultracold gas of cesium atoms [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the numerous bound-state calculations, e.g., [4,5,6,7,8,9,10,11], also the collision processes have been investigated in the framework of hyperspherical harmonics (HH) [6], coordinate-space Faddeev-Yakubovsky (FY) equations [12,8] or momentum-space Alt,Grassberger and Sandhas (AGS) equations [13,14]. The studies include the elastic and inelastic atom-trimer [8,14,15] ⋆ Dedicated to Professor Henryk Witala at the occasion of his 60th birthday A. Deltuva…”
mentioning
confidence: 99%
“…First, atomic gases provide an ideal platform for investigating phenomena related to Efimov physics [1][2][3]. While the majority of investigations of the Efimov effect have focused on the three-body system, larger systems have attracted considerable attention recently from theoretical and experimental groups [4][5][6][7][8][9][10][11][12][13][14][15]. Second, small trapped atomic systems can be realized by loading an atomic gas into an optical lattice [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%